Role of Palliative Care Nurses in Tertiary Hospitals - Subwongcharoen, Nittaya; Chintapanyakun, Teepatad (Journal of The Royal Thai Army Nurses, 2020)
The significant notion of palliative care is to establish comfort, diminish of pain, and relief of suffering, which encompassed the holistic, spiritual, and humanize care to the patients. Promoting death-with-dignity to the end-of-life patients and their family members are significant concerns either before and after the death of those patients. Integrating comprehensive care—physical, psycho-social, and spiritual care—are not only necessary to understand the nature of the deaths, but imperative to enhance the good life and the good dead. Hence, either before or after the death, nursing’s roles as a coordinator or peer supporter in alleviating physical or spiritual suffering and providing holistic care are vital keys to strengthen the quality of palliative care.